Development of a validated liquid chromatographic method for quantification of sorafenib tosylate in the presence of stress‐induced degradation products and in biological matrix employing analytical quality by design approach. (4th February 2018) - Sharma, Teenu; Khurana, Rajneet Kaur; Jain, Atul; Katare, O.P.; Singh, Bhupinder
Abstract: The current research work envisages an analytical quality by design‐enabled development of a simple, rapid, sensitive, specific, robust and cost‐effective stability‐indicating reversed‐phase high‐performance liquid chromatographic method for determining stress‐induced forced‐degradation products of sorafenib tosylate (SFN). An Ishikawa fishbone diagram was constructed to embark upon analytical target profile and critical analytical attributes, i.e. peak area, theoretical plates, retention time and peak tailing. Factor screening using Taguchi orthogonal arrays and quality risk assessment studies carried out using failure mode effect analysis aided the selection of critical method parameters, i.e. mobile phase ratio and flow rate potentially affecting the chosen critical analytical attributes. Systematic optimization using response surface methodology of the chosen critical method parameters was carried out employing a two‐factor–three‐level–13‐run, face‐centered cubic design. A method operable design region was earmarked providing optimum method performance using numerical and graphical optimization. The optimum method employed a mobile phase composition consisting of acetonitrile and water (containing orthophosphoric acid, pH 4.1) at 65:35 v/v at a flow rate of 0.8 mL/min with UV detection at 265 nm using a C18 column. Response surface methodology validation studies confirmed good efficiency and sensitivity of the developed method for analysis of SFN in mobile phase as well as in human plasma matrix. The forced degradation studies were conducted under different recommended stress conditions as per ICH Q1A (R2). Mass spectroscopy studies showed that SFN degrades in strongly acidic, alkaline and oxidative hydrolytic conditions at elevated temperature, while the drug was per se found to be photostable. Oxidative hydrolysis using 30% H2 O2 showed maximum degradation with products at retention times of 3.35, 3.65, 4.20 and 5.67 min. The absence of any significant change in the retention time of SFN and degradation products, formed under different stress conditions, ratified selectivity and specificity of the systematically developed method.